Valaciclovir versus aciclovir in patient initiated treatment of recurrent genital herpes: a randomised, double blind clinical trial. International Valaciclovir HSV Study Group. Issue 2 (April 1997) - Bodsworth, N J; Crooks, R J; Borelli, S; Vejlsgaard, G; Paavonen, J; Worm, A M; Uexkull, N; Esmann, J; Strand, A; Ingamells, A J; Gibb, A
Abstract : OBJECTIVE: To compare the efficacy and safety of twice daily valaciclovir with five times daily aciclovir in the treatment of an episode of recurrent genital herpes simplex virus (HSV) infection in immunocompetent individuals. METHODS: 739 patients with a history of recurrent genital HSV infection received either oral valaciclovir (500 mg twice daily) or aciclovir (200 mg five times daily) for 5-days for treatment of their next recurrent episode in a controlled, randomised, double blind trial. Patients self initiated therapy at the first signs and/or symptoms of the HSV recurrence, then were assessed in clinic on five occasions over 7 days, and twice weekly thereafter until lesions had healed. Safety was evaluated through adverse experience reports and haematology and biochemistry monitoring. RESULTS: No significant differences were detected between valaciclovir and aciclovir for the primary endpoint, the duration of all signs and symptoms which included lesion healing and pain/discomfort. The hazard ratio [95% confidence interval] for valaciclovir v aciclovir was 0.93 [0.79, 1.08]. Lesion healing time was similar in each treatment group (hazard ratio valaciclovir v aciclovir 0.96 [0.80, 1.14]). The odds ratio of valaciclovir v aciclovir in preventing the development of vesicular/ulcerative lesions was 1.08 [0.82, 1.42]. Percentages of patients in whom all HSV cultures were negative were similar in the valaciclovir and aciclovir groups at 59% and 54% respectively; for patients having equal to or more than one positive culture result after treatment initiation, cessation of virus shedding was similarly rapid for the two treatments (hazard ratio 0.98 [0.75, 1.27]). The safety profiles of valaciclovir and aciclovir were comparable with adverse experiences being infrequent and generally mild. CONCLUSION: This study has demonstrated that valaciclovir 500 mg twice daily is equivalent in efficacy to aciclovir 200 mg five times daily as episodic treatment of recurrent genital HSV infection. Valaciclovir maintains the established efficacy and safety of aciclovir but offers a much more convenient twice daily dosing regimen.